Convection and Conductive Heat Transfer to the Floor of Tents. - Cain,Brad (1986)
Conductive heat transfer to the floor of a single walled tent was examined experimentally and empirically, A heated, Canadian Forces, 5-Man, Arctic Tent was used to measure heat flow rates to the floor, as well as air temperatures and air velocity near the floor. The measured conductive heat flow rates to the floor of the tent were compared with predictions based on empirical correlations from problems of similar yet different geometries. Predicted heat flow rates obtained from stagnation point flow analysis were found to agree with measured heat flow rates to within 25%. The total conductive heat loss to the floor of this single walled tent was found to be approximately 7% of the total heat loss from the tent. Thus, the use of the stagnation point flow correlation would result in an error of approximately 7% of the total heat loss from the tent. Thus, the use of the stagnation point flow correlation would result in an error of approximately 2% in the calculation of the overall heat transfer rate from a single walled tent. The conductive heat flow rate to the floor was found to be approximately 20 W/sq.m and the radial air speed near the floor was found to be less than 0.1 m/s. Abstract in French.